Intensification of Wild Silkworm Attacus atlas Rearing (Lepidoptera: Saturniidae) - B K Desmawita; A M Fuah; D R Ekastuti (Media Peternakan, 2013)
Study on intensification program through reproduction and feeding management was conducted for six months to evaluate the growth and reproductive performance of wild silkworm, Attacus atlas. The experiment was divided into two phases: 1) the first phase was conducted on mating management, by applying different times of mating duration of 3, 6, 12, and 24 h as treatments to assess eggs production. In this phase, a completely randomized design was used, with 4 treatments and 5 replications; 2) the second phase was on feeding management, a completely randomized design method (2 x 2) was used, including feed (guava and walnut leaves) as first factor, and the second factor was feeding times (3 and 4 times/day) with 5 replications. The results obtained from the first experiment showed that different duration of mating significantly (P<0.05) affected the number of eggs produced. Based on time efficiency 6 hours mating duration produced higher egg production (226 egg/cycle), as well as hatchability (95%) than those of other mating duration. In the second experiment, it was found that there was interaction between feed types and feeding frequencies which significantly (P<0.05) affected feed consumption, feed digestibility, body weight gain, diameter of larvae and mortality rate. In conclusion, the optimum and efficient duration sugested for mating is six hours resulting high egg production. The walnut leaves feed has better effect on the first and second instar of larvae, while the guava leaves affect the following instars. In terms of production, four times of feeding frequency per day has higher productivity and is recommended in the cultivation management of A. atlas.